2023
DOI: 10.3390/jcdd10010025
|View full text |Cite
|
Sign up to set email alerts
|

The Cost Effectiveness of Coronary CT Angiography and the Effective Utilization of CT-Fractional Flow Reserve in the Diagnosis of Coronary Artery Disease

Abstract: Given the high global disease burden of coronary artery disease (CAD), a major problem facing healthcare economic policy is identifying the most cost-effective diagnostic strategy for patients with suspected CAD. The aim of this review is to assess the long-term cost-effectiveness of coronary computed tomography angiography (CCTA) when compared with other diagnostic modalities and to define the cost and effective diagnostic utilization of computed tomography-fractional flow reserve (CT-FFR). A search was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…99,100 The diagnosis and treatment of critical illnesses were significantly impacted between 2019 and 2023 by the use of MRI, PET, computed tomography (CT), angiography scans, other techniques, and combinations of them. 101 The surgical strategy has been improved with the use of CT, MRI, and ultrasound images. Polyurethane nanoparticles labeled with small molecular Table 4.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…99,100 The diagnosis and treatment of critical illnesses were significantly impacted between 2019 and 2023 by the use of MRI, PET, computed tomography (CT), angiography scans, other techniques, and combinations of them. 101 The surgical strategy has been improved with the use of CT, MRI, and ultrasound images. Polyurethane nanoparticles labeled with small molecular Table 4.…”
Section: Imagingmentioning
confidence: 99%
“…In recent years, multidisciplinary research has increasingly relied on the advancement of nanotechnologies for the identification of various diseases. By precisely targeting affected locations inside the body with nanomedicines, the toxicity and dosage of medications and diagnostics can be significantly lowered. , The diagnosis and treatment of critical illnesses were significantly impacted between 2019 and 2023 by the use of MRI, PET, computed tomography (CT), angiography scans, other techniques, and combinations of them . The surgical strategy has been improved with the use of CT, MRI, and ultrasound images.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…A meta-analysis including most of the above studies in patients with either acute or stable chest pain showed that anatomical testing with CCTA as the initial non-invasive diagnostic modality resulted in a lower risk of non-fatal myocardial infarction, but not MACEs or all-cause mortality, as compared with the usual care with functional testing at the expense of a more frequent use of invasive procedures [ 102 ]. Moreover, a systematic review in patients with acute or stable chest pain showed that CCTA is cost-effective when compared with the standard of care, including functional testing [ 103 ].…”
Section: Contrast-enhanced Ctmentioning
confidence: 99%